Challenges of Digital Entrepreneurship and Its Role in Women Empowerment: A Sociological Study in District Faisalabad - Nazia Malik; Fouzia Mumtaz; Shanza Kiran (Indus Journal of Social Sciences, 2025)
This study explores women’s challenges in achieving empowerment through digital entrepreneurship in the 21st century. Using a qualitative approach, data was collected via interviews with 16 female entrepreneurs in Faisalabad, Pakistan. Thematic analysis identified key challenges, including limited access to finance, lack of family support and mentorship, difficulty finding vendors and riders, family disturbances, health issues, overburden, networking barriers, gender biases, and inadequate skill development. The study suggests targeted financial support, mentorship programs, policy reforms, awareness campaigns, and tailored skill development initiatives to address these. It advocates for an inclusive digital entrepreneurial ecosystem, ensuring women’s active participation and empowerment.